TRAINING END USERS TO SEARCH ONLINE: BASIC SKILLS AND PRACTICAL CONSIDERATIONS/LA FORMATION DES USAGERS A LA RECHERCHE EN ACCES-DIRECT: COMPETENCE DE BASE ET CONSIDERATIONS D'ORDRE PRATIQUE - Grande, Sally (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF